2021
DOI: 10.1002/mrm.28788
|View full text |Cite
|
Sign up to set email alerts
|

A self‐decoupled 32‐channel receive array for human‐brain MRI at 10.5 T

Abstract: Purpose Receive array layout, noise mitigation, and B0 field strength are crucial contributors to SNR and parallel‐imaging performance. Here, we investigate SNR and parallel‐imaging gains at 10.5 T compared with 7 T using 32‐channel receive arrays at both fields. Methods A self‐decoupled 32‐channel receive array for human brain imaging at 10.5 T (10.5T‐32Rx), consisting of 31 loops and one cloverleaf element, was co‐designed and built in tandem with a 16‐channel dual‐row loop transmitter. Novel receive array d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…0.46 or ~0.5 mm isotropic resolution). We demonstrate here that this goal is achieved with NORDIC (Figure 6) at 7 Tesla and likely will soon be surpassed when multiplicative gains will be attained combining NORDIC with additional independent gains from acquisition methods, higher magnetic fields 52 , high channel count RF coils employed synergistically with very high magnetic fields 53,54 and image reconstructions methods (e.g. 55,56 ).…”
Section: Discussionmentioning
confidence: 86%
“…0.46 or ~0.5 mm isotropic resolution). We demonstrate here that this goal is achieved with NORDIC (Figure 6) at 7 Tesla and likely will soon be surpassed when multiplicative gains will be attained combining NORDIC with additional independent gains from acquisition methods, higher magnetic fields 52 , high channel count RF coils employed synergistically with very high magnetic fields 53,54 and image reconstructions methods (e.g. 55,56 ).…”
Section: Discussionmentioning
confidence: 86%
“…We demonstrate here that this goal is achieved with NORDIC (Fig. 6) at 7 T and likely will soon be surpassed when multiplicative gains will be attained combining NORDIC with additional independent gains from acquisition methods, higher magnetic fields 52 , high channel count RF coils employed synergistically with very high magnetic fields 53,54 and image reconstructions methods (e.g. refs.…”
Section: S1mentioning
confidence: 86%
“…These studies have shown improvements in simulations and have a promising prospect once they are fully implemented experimentally. These increases in signal-to-noise ratio (such as reported in [26]) are substantial progress towards empowering neuroscience research applications targeting human brain [31].…”
Section: Hardware Advancesmentioning
confidence: 99%
“…Most recently, the concept of self-decoupling was introduced [25]. Other researchers [26] brilliantly developed the self-decoupling concept to simplify the design of receive arrays and also demonstrated experimentally that self-decoupling provides an SNR advantage compared to overlap-decoupling. The latter stands as a much anticipated breakthrough that obviates the complexities of building high density receive arrays.…”
Section: Hardware Advancesmentioning
confidence: 99%